Bioinspired micro-structured fibers for biomedical applications - Jiahui Guo; Shuangshuang Miao; Lingyu Sun; Yuanjin Zhao; Xiaosong Gu (Bioactive Materials, 2025)
Fibers, which are common in nature, have been playing an integral role in the life of mankind ranging from traditional textile industries to modern medical fields. Inspired by the spinning process of spider/silkworm, impressive advancements have been achieved in the design and development of bioinspired fiber materials with diverse microstructures. In this review, we provide an overall summarization into the latest progress in the structures and applications of bioinspired fibers. Following an introduction to natural fiber systems (e.g., spider silk, silkworm silk, and muscle structures), we focus on the fabrication methods and characterization techniques for the preparation of bioinspired fibers with tailored structures. Emphasis is also given to the summarization of their biomedical applications. Furthermore, some insights into the challenges and even opportunities that need to be faced in the future development process are given.